PEMBERDAYAAN KETERAMPILAN MENJAHIT TANGAN MASYARAKAT DESA BAJANG PADA MASA PANDEMI MELALUI PELATIHAN PEMBUATAN MASKER KAIN - rahayu, eka puji; Effendi, Mukhlison (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
The Community Service Lecture activity held in Doplang hamlet, Bajang village was carry out using the ABCD (Asset Based Community Development) approach. There are few methods that have been taken in the field like introduction (Inculturation), revealing information (Discovery), knowing assets and identifying opportunities (Design), supporting the implementation of work programs (Define), and reflection (Reflection). The purpose of this Community Service activity is to develop the assets owned by the Doplang hamlet community, namely hand sewing skills. The housewives in the Doplang hamlet are the owner of these skills indeed. Based on the discovery of these assets, the servant took the initiative to develop the skills possessed by the Doplang hamlet women. Related to the current pandemic, where masks are mandatory in carrying out mask activities, the cloth-making training activity was chosen to develop the hand sewing skills of women in Doplang hamlet, Bajang village. Based on the evaluation that had been carried out, the training activities are considered to be successful in developing the sewing skills of the Doplang hamlet community. This could be seen from the successfull of training activities and public awareness of the potential development of assets owned. In the future, it is hoped that these skills can continue to developing, both independently and in groups of the Doplang hamlet women to make cloth masks or other innovations in the continued development of existing assets in the community.